HARMONISASI STRATEGI BERSAING KONTRAKTOR NASIONAL SKALA BESAR DALAM MENGHADAPI MEA - eddy irsan siregar; siddik siregar (Jurnal Ilmiah Ekonomi Dan Bisnis, 2017)
Abstract: At the beginning of January 2016, the Era of the ASEAN Economic Community (MEA) has been enacted and will lead to regional level competition changes in ASEAN, this will impact on competitive strategies implemented by the National Contractors. The purpose of this paper is to know the alignment of competitive strategies of National Contractors in the era of MEA based on Innovation Management, the unique characteristics of resources, and competitive advantage that affect the competitive strategy. This research method is done by using conceptual framwork models by comparing previous literature and research studies and using tested model diagrams. SWOT analysis is used for quantitative evaluation. The sample was distributed to 30 respondents as decision makers of all National Contractors. It was found that the uniqueness of resources is quite common and it is also found that competitiveness is inbetween zones or has low competitive advantage. So the action of competitive strategy that must be done is cooperation strategy (cooperative strategy) among construction industry actors in ASEAN countries.Keywords: Innovation Management, Unique Resources, Competitive Strategy, Competitive Advantage